Treatment outcomes and secondary cancer incidence in young patients with hairy cell leukaemia. (28th June 2016) - Getta, Bartlomiej M.; Woo, Kaitlin M.; Devlin, Sean; Park, Jae H.; Abdel‐Wahab, Omar; Saven, Alan; Rai, Kanti; Tallman, Martin S.
Summary: Repeated therapy of hairy cell leukaemia (HCL) with treatments that have potential long‐term toxicities has raised concerns regarding increased risk for younger patients. We compared clinical outcomes and disease complications in 63 patients with HCL aged ≤40 years at diagnosis with 268 patients >40 years treated at Memorial Sloan Kettering Cancer Center. The rate of complete remission following initial therapy was 87% and 83% ( P = 0·71) and estimated 10‐year overall survival was 100% and 82% ( P = 0·25) in younger and older patients, respectively. Younger patients required therapy earlier and had a significantly shorter time between first and second therapy (median: 63 months vs. 145 months) ( P = 0·008). Younger patients required significantly more lines of therapy during follow‐up. The 10‐year cumulative incidence of secondary malignancies in young and old patients was 0·205 and 0·287, respectively ( P = 0·22). The incidence of secondary cancers in patients aged >40 years at diagnosis increased with the number of treatments for HCL ( P = 0·018). These results highlight that young patients with HCL have shorter responses to treatment and require more lines of therapy to maintain disease control, while attaining similar long‐term survival. This has implications in the design of future clinical trials given our findings that secondary malignancies increase with more chemotherapy exposure.